The risk and associated factors of methamphetamine psychosis in methamphetamine-dependent patients in Malaysia - Sulaiman, A.H.; Said, M.A.; Habil, M.H.; Rashid, R.; Siddiq, A.; Guan, N.C.; Midin, M.; Jaafar, N.R.N.; Sidi, H.; Das, S. (2014)
Objective: The objective of this study was to determine the risk of lifetime and current methamphetamine-induced psychosis in patients with methamphetamine dependence. The association between psychiatric co-morbidity and methamphetamine-induced psychosis was also studied. Methods: This was a cross-sectional study conducted concurrently at a teaching hospital and a drug rehabilitation center in Malaysia. Patients with the diagnosis of methamphetamine based on DSM-IV were interviewed using the Mini International Neuropsychiatric Interview (M.I.N.I.) for methamphetamine-induced psychosis and other Axis I psychiatric disorders. The information on sociodemographic background and drug use history was obtained from interview or medical records. Results: Of 292 subjects, 47.9 of the subjects had a past history of psychotic symptoms and 13.0 of the patients were having current psychotic symptoms. Co-morbid major depressive disorder (OR = 7.18, 95 CI = 2.612â19.708), bipolar disorder (OR = 13.807, 95 CI = 5.194â36.706), antisocial personality disorder (OR = 12.619, 95 CI = 6.702â23.759) and heavy methamphetamine uses were significantly associated with lifetime methamphetamine-induced psychosis after adjusted for other factors. Major depressive disorder (OR = 2.870, CI = 1.154â7.142) and antisocial personality disorder (OR = 3.299, 95 CI = 1.375â7.914) were the only factors associated with current psychosis. Conclusion: There was a high risk of psychosis in patients with methamphetamine dependence. It was associated with co-morbid affective disorder, antisocial personality, and heavy methamphetamine use. It is recommended that all cases of methamphetamine dependence should be screened for psychotic symptoms.